Improving Islamic Religious Education Learning through the Method of Giving Learning Assignments and Recitations at SD Negeri 0211 Pasar Binanga - Nasution, Nuraida; Harahap, Damriah (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2025)
This study aims to determine the effect of the method of giving learning assignments and recitations in improving Islamic Religious Education (PAI) learning in students of SD Negeri 0211 Pasar Binanga, Barumun Tengah District, Padang Lawas Regency. The method used in this study is an experimental method with a pretest-posttest group design. This study was conducted on fifth grade students with a sample of 30 students who were divided into two groups: the experimental group who were treated with the method of giving learning assignments and recitations, and the control group who were given conventional learning. Data collection was carried out through written tests and observations during the learning process. The results of the study showed that the application of the method of giving learning assignments and recitations significantly improved student learning outcomes in the subject of Islamic Religious Education. This is evidenced by the significant difference between the pretest and posttest scores in the experimental group, while the control group did not show a significant increase. In addition, students who participated in learning with this method were more active and motivated in learning and were better able to understand the material being taught. Thus, it can be concluded that the method of giving learning assignments and recitations can improve Islamic Religious Education learning outcomes in SD Negeri 0211 Pasar Binanga.